Pengaruh Manajemen Laba Akrual dengan Pendekatan Revenue Discretionary Model terhadap Kinerja Perusahaan - Sepriahangga Wahyu Windharta; Nurmala Ahmar (Faculty of Economics and Business, University of Pasundan, 2014)
Accrual earnings management is a form of manipulation of financial statements on the accrual components to increase its profit in order to look good in the investors perception. This research approach discretionary revenue published by Stubben in 2010 with two different formulas are conditional revenue models and revenue models to measure the accrual earnings management to be proxies to the performance of the company. The purpose of this study was to analyze the effect of accrual earnings management by discretionary revenue approach on firm performance in manufacturing companies listed on the Stock Exchange. The Results of analysis for this study were 1) Accrual earnings management is measured using a Revenue Model does not affect the Return On Asset. 2) Accrual earnings management is measured using a Revenue Model does not affect the Tobin’s q. 3) Accrual earnings management is measured using a Conditional Revenue Models effect on the Return On Asset. 4) Accrual earnings management is measured using a Conditional Revenue Models has no effect on Tobin’s q.